2020
DOI: 10.3389/fvets.2020.539925
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Pathogen Transmission at the Backyard Chicken–Wild Bird Interface

Abstract: Habitat conversion and the expansion of domesticated, invasive species into native habitats are increasingly recognized as drivers of pathogen emergence at the agricultural-wildlife interface. Poultry agriculture is one of the largest subsets of this interface, and pathogen spillover events between backyard chickens and wild birds are becoming more commonly reported. Native wild bird species are under numerous anthropogenic pressures, but the risks of pathogen spillover from domestic chickens have been histori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 277 publications
(265 reference statements)
0
45
0
Order By: Relevance
“…Although high prevalence was reported for Orinithobacterium rhinotracheale (ORT − 96%), Leucocytozoan (69%) and chicken infectious anemia (CIA − 53%), the number of studies was meagre. Mycoplasma gallisepticum (MG) and Mycoplasma Synoviae (MS) are commonly found in backyard chickens and the most notable bacterial pathogens that have spread from backyard chicken to wild birds (Ayala et al, 2020). Avian in uenza (AI) was the most reported disease worldwide followed by Newcastle disease (ND) in backyard poultry in the present meta-analysis.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Although high prevalence was reported for Orinithobacterium rhinotracheale (ORT − 96%), Leucocytozoan (69%) and chicken infectious anemia (CIA − 53%), the number of studies was meagre. Mycoplasma gallisepticum (MG) and Mycoplasma Synoviae (MS) are commonly found in backyard chickens and the most notable bacterial pathogens that have spread from backyard chicken to wild birds (Ayala et al, 2020). Avian in uenza (AI) was the most reported disease worldwide followed by Newcastle disease (ND) in backyard poultry in the present meta-analysis.…”
Section: Discussionmentioning
confidence: 79%
“…Earlier studies also reported 34% and 40% seropositivity in unvaccinated backyard chickens in Vietnam and Iran, respectively (Vui et al, 2002;Saadat et al, 2014). Nevertheless, backyard chicken is considered as potential source of reservoir for pathogen spill over including ND and spread to wild birds (Ayala et al, 2020).…”
Section: Discussionmentioning
confidence: 95%
“…Wild birds are often suspected to be the source of a disease incursion into farm animals, although domestic and wild birds share the same environment, and both may get infected from similar environmental sources, or pathogen transmission may consist of spill‐over and spill‐back events among wildlife, livestock and humans. 29 The present study investigated wild birds as possible carriers of Salmonella as a potential hazard to livestock and humans ‐ specifically the workers of the bird rehabilitation centre. Sampling was limited to a small geographic region, due to the fact, that wild birds were not sampled in the field, but were sampled in a resource‐effective manner after admittance to a rehabilitation centre.…”
Section: Discussionmentioning
confidence: 99%
“…In most of those cases, the disease does not cause apparent symptoms in the wildlife host but can have devastating impacts on livestock populations. Examples include wild waterfowl acting as reservoirs of highly pathogenic avian influenza viruses ( Globig et al, 2009 ), wild birds as reservoirs of Newcastle Disease viruses for domestic chickens ( Ayala et al, 2020 ), warthogs being able to act as reservoirs of ASFV, and the African buffalo that is well known as the major wild reservoir of FMDV ( Jori and Etter, 2016 ; Jori et al, 2021a ). Direct or indirect contacts of such reservoirs with susceptible livestock populations can initiate sporadic outbreaks that can develop into epidemics as disease spreads between farms.…”
Section: The Impacts Of Wildlife On Livestockmentioning
confidence: 99%